A hierarchical hydrophilic/hydrophobic cooperative fog collector possessing self-pumped droplet delivering ability. Issue 42 (17th October 2018) - Bai, Haoyu; Zhang, Chunhui; Long, Zhiyun; Geng, Hui; Ba, Teer; Fan, Yangyang; Yu, Cunming; Li, Kan; Cao, Moyuan; Jiang, Lei
Abstract : Continuous and spontaneous fog harvesting, including efficient capture, one-way droplet delivery, and rapid water storage, is achieved in one step. Abstract : Harvesting micro-droplets from fog flow has emerged as a promising strategy for supplying clean water in foggy but arid regions. Ideal fog harvesting devices should possess both high efficiency for fog collection and an economic process of water accumulation. To optimize the water transporting pathway in gravity-driven fog collectors, here we present a hierarchical hydrophilic/hydrophobic (3H) cooperative fog collecting surface with the function of self-pumped droplet absorption. The directional water delivery completely depends on the surface energy release of the hanging droplets with a spherical shape. This 3H fog harvesting surface, composed of upright steel needles, hydrophilic foam of melamine resin and hydrophobic silica stripes, exhibits enhanced fog collecting ability, i.e., four times higher than that of the pristine hydrophilic foam surface and two times higher than that of the hydrophilic/hydrophobic surface without a hierarchical structure. More importantly, the pathway of water preservation is improved to overcome the drawback of traditional systems. Fog-water can be effectively captured by the protrusion structure and subsequently absorbed by the hydrophilic foam driven by the wettability gradient. Further incorporation of striped water barriers promotes one-way water transport even against gravity. Propelled by the surface energy, this 3H fog collector can achieve a gravity-independent process of efficient fog capture, directional water delivery, and rapid water storage all in one step. This design gives an example of advanced fog harvesting interfaces and can extend the application scope of self-propelled fluid delivery systems.